Long-term efficacy of T3 analogue Triac in children and adults with MCT8 deficiency: a real-life retrospective cohort study - DEMİRCİOĞLU, SERAP (My University, 2021)
CONTEXT: Patients with mutations in thyroid hormone transporter MCT8 have developmental delay and chronic thyrotoxicosis associated with being underweight and having cardiovascular dysfunction. Our previous trial showed improvement of key clinical and biochemical features during one year of treatment with the T3-analogue Triac. Long-term follow-up data are lacking. METHODS: In this real-life retrospective cohort study, we investigated the efficacy of Triac in MCT8 deficient patients in 33 sites. The primary endpoint was the change in serum T3 concentrations from baseline to last-available measurement. Secondary endpoints were changes in other thyroid parameters, anthropometric parameters, heart rate, and biochemical markers of thyroid hormone action. RESULTS: Between 15-Oct-2014 and 1-Jan-2021, sixty-seven patients with a median baseline age of 4.6 years (range:0.5-66 years) were treated up to 6 years, with a median of 2.2 years (range 0.2-6.2 years). Mean T3 concentrations decreased from 4.58 (SD:1.11) to 1.66 (0.69) nmol/L (mean decrease 2.92 nmol/L, 95%CI:2.61-3.23, p<0.0001; target:1.4-2.5 nmol/L). Body weight-for-age exceeded that of untreated historical controls (mean difference 0.72 SDs, 95%CI:0.36-1.09, p=0.0002). Heart rate-for-age decreased (mean difference 0.64 SDs, 95%CI:0.29-0.98, p=0.0005). SHBG concentrations decreased from 245 (99) to 209 (92) nmol/L (mean decrease 36 nmol/L, 95%CI:16-57, p=0.0008). Mean creatinine concentrations increased from 32 (11) to 39 (13) µmol/L (mean increase 7 µmol/L, 95%CI:6-9, p<0.0001). Mean CK concentrations did not significantly change. No drug-related severe adverse events were reported. CONCLUSIONS: Key features were sustainably alleviated in patients with MCT8 deficiency across all ages and highlight the potential of Triac for MCT8 deficiency in real-life.
Keywords: AHDS; Allan-Herndon-Dudley syndrome; MCT8 Deficiency; T3 analogue; thyromimetic drug